Perbedaan Individual pada Ideologi Politik Berbasis Agama - Amalia, Ilmi (Fakultas Psikologi UIN Syarif Hidayatullah Jakarta, 2020)
In practicing worship almost all Muslims run in the same manner but in Indonesia also found the diversity of the face of Islam. One form of diversity is how to see religion as a political ideology. From various views political ideologies based on Islamic religion have polarizations, namely secular and radical Islamism. How to explain the diversity of ideologies based on individual differences. Jost et al (2009) offer three basic needs that determine individual ideological differences, namely the need for epistemic, the need for existential, and the need for relational. In addition to differences in the concept of fundamental needs, studies also show a relationship between personality types and ideological or political attitudes. Duckitt & Sibley (2010) offers a dual-process motivational model that explains that political ideology is formed due to interactions between personalities and different social situations. Many studies have been conducted to see the relationship between ideology with liberal and conservative polarization (right / left) or right wing authoritarianism (RWA) and social dominance orientation (SDO) with different needs or personality types (Jost, Ledgerwood, & Hardin, 2008; Jost et al., 2007; Sibley, Osborne, & Duckitt, 2012). However, no research has been conducted on political ideologies based on religion, especially Islam. The study was conducted on 243 Muslims and aged 17 years and over. Questionnaires were distributed in the Greater Jakarta area online and offline. The sampling technique used convenience sampling. Then the data is processed using regression analysis techniques. The results showed that together, the need for epistemic, need for existential, need for relational, and Big five personality influenced Islamic political ideology with a contribution of 7.2%. Significant predictors of the relationship are need for existential and need for relational.